2015
DOI: 10.7763/ijssh.2015.v5.434
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Knowledge Sharing Practices among Paddy Farmers towards Building a Foundation for Knowledge Creation

Abstract: Abstract-The importance of knowledge sharing within a country whether at central, regional nor local governments has been largely overlooked. In a knowledge based economy, performance and productivity are the factors that crucial in determining success factors. This is an indicator of the sustainability of economic development. Competencies, skills and knowledge are the imperative components to achieve the competitive advantage for individual and organization. Learning becomes as an important activity to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Knowledge sharing behaviour among employees has been associated with organization’s overall productivity (Naoman and Fouad, 2014), and therefore, the agricultural industry’s productivity can be further improved if farmers exchange useful knowledge with one another. This is because previous studies have suggested that successful farmers have adequate knowledge to boost their productivity (Kamarudin et al , 2015). Knowledge sharing behaviour among successful farmers is of concern not only on the farmers’ development but also on the the performance of the Department of Agriculture as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge sharing behaviour among employees has been associated with organization’s overall productivity (Naoman and Fouad, 2014), and therefore, the agricultural industry’s productivity can be further improved if farmers exchange useful knowledge with one another. This is because previous studies have suggested that successful farmers have adequate knowledge to boost their productivity (Kamarudin et al , 2015). Knowledge sharing behaviour among successful farmers is of concern not only on the farmers’ development but also on the the performance of the Department of Agriculture as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge is the bedrock of innovation and sustainability amongst smallholder farmers in Africa. Indeed, Kamarudin et al (2015) argue that indigenous knowledge as well as personal experiences of farmers are essential sources of original and contextual knowledge and should be shared widely for effective productivity. Chepchirchir et al (2019) explain that indigenous knowledge plays a pivotal role in crop farming, pastoralism, fishing and environmental conservation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ramirez and Reyes (2013) suggest that farmers who are keen on ICTs should be trained and used as peer trainers to enhance the uptake of ICT-based solutions in sharing farming knowledge. Kamarudin et al (2015) aver that effective knowledge sharing is a significant contributor to increased agricultural productivity. Therefore, farmers require both tacit and explicit knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Information sharing is meaningful exchange of ideas, facts and opinions between two or more people to bring significant behavioural change (Hilary et al, 2017;Kamarudin et al, 2015). It involves both sharing of information by the source; and acquiring and applying of information by the recipient (Mtega and Ngoepe, 2018) Information is the facts or message of something such as an innovation, an organization, service or an event that provided from the sources to receivers (David and Cofini, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%